Cyclical price fluctuations caused by information inertia : evidence from the German call-by-call telephone market - Antje Baier; Friedel Bolle (European University Viadrina, Department of Business Administration and Economics, 2005)
The 2002 prices of suppliers in German call-by-call telephone market are rather dispersed, out-of-phase (uncorrelated), and show systematic down-up movements. In 2004, these prices are less dispersed, more in-phase and show more upwards runs than downs-ups. In both years, we clearly do not observe Edgeworth cycles where prices move in parallel (in-phase). We present a model with demand inertia, caused by incomplete information about prices, where (out-of-phase and in-phase) cycles as well as competitive equilibria and tacit collusion equilibria exist. The transition from the 2002 cycles in the German call-by-call market to more constant prices in 2004 may be due to parameter changes, such as customers possessing improved information.
Keywords: D43; C73; 330; Price cycles; incomplete information; telephone market; Telekommunikationsgebühr; Volatilität; Cobweb; Unvollkommene Information; Konsumentenverhalten; Informationsverhalten; Theorie; Deutschland